Tackling poverty at its roots: a case study of skills development in integrated conservation and development with the example of the Working For Water programme - Rönchen, Ann-Kristina (Department of Sociology, 2014)
The South African government has been challenged to combat persistently high rates of structural unemployment and poverty among parts of the previously disadvantaged population since the country's political transition in the 1990s. One policy response is the introduction of the Expanded Public Works Programme (EPWP), which seeks to alleviate poverty by providing labour-intensive work opportunities for the unemployed in the sectors of infrastructure, environment and culture, economics and in the social sector. In 2014 the second phase of the EPWP will come to a close. The environmental sector of the EPWP addresses issues of biodiversity conservation and natural resource management, and offers work opportunities in programmes such as the Working for Water (WfW) programme. South Africa is one of the most bio-diverse countries in the world and a pioneer in the control of invasive alien plants (IAPs). The WfW programme provides work opportunities and training for beneficiaries and contractors to control IAPs, using biological, mechanical and chemical methods. Skills development in the EPWP is regarded as a key factor to overcome unemployment and poverty on a long-term basis. Using the case study of the Citrusdal Water Users Association (CWUA), a project of the WfW programme, this thesis analyses to what extent and of what developmental value the environmental EPWP fulfills its objective of skills development. The training model of the WfW programme in the Western Cape, with special focus on the project CWUA, serves as analytical tool. Data was collected through qualitative interviews among WfW officials of the Western Cape Regional and the National Office, and supported by a questionnaire among 79 beneficiaries of the CWUA project using closed dichotomous questions. Furthermore, the research was informed through the review of internal WfW documents such as training matrix, training strategy and literacy assessment results of beneficiaries, as well as a questionnaire conducted by WfW officials and analysed by the researcher. The thesis has found that the training model currently in place deals only with the symptoms of poverty and that the relief is of temporary nature. Skills development ends at the programme boundaries and has little impact on the beneficiaries' enhancement of future employability. The model does not make full use of its potential to contribute to longterm reduction of unemployment. Reasons are found in the multi-objective context of nature conservation, job creation and skills development, which leads to the neglect of the latter. This research adds to the literature of Integrated Conservation and Development (ICD) on a governmental level and questions whether interventions such as the EPWP contribute to the socio-economic development of the South African population from a long-term perspective.